2008
DOI: 10.1242/jcs.024646
|View full text |Cite
|
Sign up to set email alerts
|

Growth arrest in human T-cells is controlled by the non-coding RNA growth-arrest-specific transcript 5 (GAS5)

Abstract: There was an error published in J. Cell Sci. 121, 939-946.The reverse primer sequence for RT-PCR in the Materials and Methods is given in the 3¢-to-5¢ direction, not the 5¢-to-3¢ direction as stated. The correct sequence of the reverse primer is 5¢-TCTTGTGCCATGAGACTCCATCAG-3¢.The authors apologise for this error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
162
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(176 citation statements)
references
References 27 publications
14
162
0
Order By: Relevance
“…Induction of apoptosis was not dependent on the presence of the ORF, as GAS5-2B does not include the ORF (MourtadaMaarabouni et al, 2008). This lack of dependence on the ORF, which is also seen for GAS5 transcripts expressed in human T-cell lines (Mourtada-Maarabouni et al, 2008), is consistent with GAS5 acting as a noncoding RNA (Mattick, 2005). SnoRNAs similar to those in the GAS5 introns are involved in ribosomal RNA processing (Kiss, 2002), and may have other, as-yet undefined functions (Matera et al, 2007), which could account for the striking functional effects of GAS5 expression.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Induction of apoptosis was not dependent on the presence of the ORF, as GAS5-2B does not include the ORF (MourtadaMaarabouni et al, 2008). This lack of dependence on the ORF, which is also seen for GAS5 transcripts expressed in human T-cell lines (Mourtada-Maarabouni et al, 2008), is consistent with GAS5 acting as a noncoding RNA (Mattick, 2005). SnoRNAs similar to those in the GAS5 introns are involved in ribosomal RNA processing (Kiss, 2002), and may have other, as-yet undefined functions (Matera et al, 2007), which could account for the striking functional effects of GAS5 expression.…”
Section: Discussionmentioning
confidence: 59%
“…For the breast epithelial MCF-7 and HEK 293T cell lines, overexpression of some GAS5 ESTs induced apoptosis without any additional stimulus (Figures 4b and 5a). This effect is also seen in leukemic and untransformed human lymphocytes induced to overexpress GAS5 (Mourtada-Maarabouni et al, 2008), and these studies also showed that reduction in endogenous GAS5 levels with siRNAs produces resistance to apoptosis (Mourtada-Maarabouni et al, 2008), indicating that the effects observed are not artifacts of overexpression. There were clear differences in the caspase dependency of apoptosis induced by different GAS5 transcripts (Figures 4g and h).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Although the functions of the overwhelming majority of lncRNAs are still unknown, a small characterized fraction seems to play very diverse roles in genomic imprinting (31), chromosome X dosage compensation (32), growth arrest (33), control of pluripotency and differentiation (34), apoptosis (35), gene expression (36) and DNA methylation (37), to name just a few.…”
Section: Introductionmentioning
confidence: 99%
“…Korpal et al have shown that the miR-200 status predicts predisposition of the cancer to successful metastasis [119]. Small nucleolar RNAs (snoRNAs) have, for many years, been considered one of the bestcharacterized classes of non-coding RNAs (ncRNAs) [120][121][122][123] but despite the common assumption that snoRNAs only have cellular housekeeping functions, in the past few years, independent reports have converged in implicating snoRNAs in the control of cell fate and oncogenesis [124][125][126][127][128][129][130]. SnoRNAs are small RNAs of 60-300nt in lenght that specifically accumulate in the nucleolar compartment of the cell where are in charge of the 2′-O-ribose methylation and pseudouridylation of specific ribosomal RNA nucleotides, essential modification for the efficient and accurate production of the ribosome [120][121][122].…”
Section: Metastamirsmentioning
confidence: 99%